"Strong, yet we are vulnerable": role of psychological factors and financial affluence on women's entrepreneurial success. (2018) - Chakraborty, Tanusree; Gupta, Dishari; Chatterjee, Bipasha
For women entrepreneurs, the journey of entrepreneurship in not very easy. They need to balance work and family plus sustain business. Encountering a wide range of challenges, they sail through the path and move towards their business success. How can they do so? In this context, the present study will explore the role of psychological factors of locus of control, proactivity and personal efficacy in relation to success and failure of women established enterprises. 200 women entrepreneurs were studied by using questionnaires and in-depth interviews. The results suggest that locus of control is found to be internal in successful women, proactivity and personal-efficacy are high. Non-affluent entrepreneurs have higher levels of proactivity and personal efficacy compared to their counterparts. The variables of proactivity, personal efficacy, locus of control (LOC) and the financial conditions of the women entrepreneurs significantly impact success and failure in their ventures.